2007
DOI: 10.1310/hct0806-371
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sex Differences of Fosamprenavir (With and Without Ritonavir) in HIV-Infected Men and Women

Abstract: The absence of major sex differences provides reassurance, but the small number of women in these trials limited the ability to draw conclusions. Future trials should be specifically powered to detect sex differences in safety and efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The Context Study, which assessed treatment-experienced patients, reported a discontinuation rate of 47% in women compared with 22% in men; however, women comprised only 15% of the 315 patients enrolled, limiting the interpretation of these data. 9 Additionally, in a study that enrolled 254 patients, including a high proportion of women (50%), black (40%), and Hispanic (37%) treatment-naïve patients, Kumar et al 18 reported an overall discontinuation rate of 49%; specific differences by sex were not reported. The Women First Study was specifically designed to assess the efficacy and safety of combination ARV therapy in protease inhibitor-naïve women and also to evaluate treatment compliance and continued study participation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Context Study, which assessed treatment-experienced patients, reported a discontinuation rate of 47% in women compared with 22% in men; however, women comprised only 15% of the 315 patients enrolled, limiting the interpretation of these data. 9 Additionally, in a study that enrolled 254 patients, including a high proportion of women (50%), black (40%), and Hispanic (37%) treatment-naïve patients, Kumar et al 18 reported an overall discontinuation rate of 49%; specific differences by sex were not reported. The Women First Study was specifically designed to assess the efficacy and safety of combination ARV therapy in protease inhibitor-naïve women and also to evaluate treatment compliance and continued study participation.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,8 In contrast, post hoc analyses of several other studies have not identified sex-based differences in the efficacy and safety of ARV therapy; however, these studies were not designed for sex-based comparisons. [9][10][11] Although the number of 1 Tibotec Therapeutics, Titusville, New Jersey. 2 The Well Project, Inc., Nellysford, Virginia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fasting triglyceride elevations were more common in men than women, as has been observed in other ARV trials that enrolled either treatment-naïve or treatment-experienced patients. [4][5][6][7] The incidence of LDL elevations was numerically higher in women than men; this is supported by the cross-sectional FRAM (Fat Redistribution And Metabolic change) study, which recently demonstrated that HIV-infected women had higher LDL levels compared to uninfected women. In contrast, HIV-infected men had lower LDL levels than uninfected men, 13,14 suggesting the LDL elevations may be more prevalent in HIV-infected women than men.…”
Section: Discussionmentioning
confidence: 92%
“…[4][5][6][7] For instance, men receiving ARV therapy are more commonly reported to develop hypertriglyceridemia compared to women. [5][6][7] Few of these trials, however, have enrolled a population of women large enough to draw definitive genderbased conclusions regarding metabolic effects of individual ARV agents.…”
Section: Introductionmentioning
confidence: 99%